2022
DOI: 10.1007/s10840-022-01266-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of advanced age with procedural complications and in-hospital outcomes from left atrial appendage occlusion device implantation in patients with atrial fibrillation: insights from the National Inpatient Sample of 36,065 procedures

Abstract: Background Age-stratified analyses of atrial fibrillation (AF) patients undergoing percutaneous left atrial appendage occlusion (LAAO) are limited. The purpose of current study was to compare in-hospital outcomes in elderly AF patients (age > 80 years) to a relatively younger cohort (age £ 80 years) after LAAO. Methods Data were extracted from National Inpatient Sample for calendar years 2015–2018. LAAO device implantations were identified on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Eighteen studies were excluded because no outcomes of interest were provided. Finally, 12 articles—11 observational studies and 1 analysis matched on propensity scores—were used in our study [ 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The characteristics of the study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies were excluded because no outcomes of interest were provided. Finally, 12 articles—11 observational studies and 1 analysis matched on propensity scores—were used in our study [ 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The characteristics of the study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our meta-analysis showed that elderly patients had a higher risk of periprocedural mortality. Although only one study in our included study found a greater risk of death in the elderly group [ 14 ], this study was excluded by sensitive analysis, and the statistical results remained statistically significant. Only one study clearly gave the cause of death: one procedure-related death occurred the next day [ 17 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 15 , 16 In a study of 6779 patients undergoing percutaneous LAAO, Sanjoy and colleagues 61 showed that older patients (≥80 years old) had a higher rate of major adverse events compared to a younger LAAO cohort (6% vs 4.6%, P < .01). Our own work 62 assessed important outcomes of inpatient mortality and major complications after LAAO in patients aged ≥80 years and compared them to a cohort of patients aged <80 years. Outcomes depicted higher adjusted mortality in older patients undergoing LAAO compared to a relatively younger cohort (OR 4.44, 95% CI 2.39–8.24), but no significant adjusted risk of major complications, prolonged length of stay, and increased hospitalization costs.…”
Section: Introductionmentioning
confidence: 99%